Mandados de criminalização e o Artigo 205 do Código Penal Militar - Santos, Eric de Assis (2013)
The present work being performed is based on the warrants of criminalization, the study of Military Criminal Code Article 205, and its relation to Federal Law No. 8072/90, exploring all the aspects necessary to ensure that changes aimed at the cataloguing of heinous crimes are carried out. The research has been divided into eight parts. In the first part, we made a brief statement about legislation, military justice in Brazil and within the world, inserting our research in the current reality of Military Law, which has been ignored by our representatives, specifically the Legislative Power. Following this contextualization, we cover general aspects concerning homicidal crimes, including its elements, jurisdictions, legal objectives and certain peculiarities related to Military Justice. The third part of our research has been devoted to the classification and differentiation of military crime in relation to common crime, dealing with the diversity of denominations used by the doctrine, addressing the conditions and concepts of proper/improper military crime. Chapters four, five and six adress the warrants of criminalization, the manner the subject is dealt in Brazil and on Compared Law. Equality Principle is the subject developed on the chapter seven. The final section of the paper discusses various issues arisen in our observation of the Heinous Crimes Law, including specific kinds of homicide, however, murder in the first degree of Military Criminal Code was not found, existing insufficient protection of a warrant criminalization